2017
DOI: 10.1088/1361-6668/aa572a
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of ultrathin niobium nitride films grown by atomic layer deposition

Abstract: We studied and optimised the properties of ultrathin superconducting niobium nitride films fabricated with a plasma-enhanced atomic layer deposition (PEALD) process. By adjusting process parameters, the chemical embedding of undesired oxygen into the films was minimised and a film structure consisting of mainly polycrystalline niobium nitride with a small fraction of amorphous niobium oxide and niobium oxo-nitrides were formed. For this composition a critical temperature of 13.8 K and critical current densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 19 publications
3
34
0
1
Order By: Relevance
“…Extremely interesting results (Tc: ~14 K for the ~30 nm thick film) have been reported using TBTDEN/H 2 [15,18] or TBTDEN/H 2 /N 2 [17,19]. Several authors [14,18] reported that the films may contain relatively high amounts of oxygen and carbon, up to 50 at%. However, high impurity levels make it difficult to make definite conclusions on the relationship between material properties and the superconductivity.…”
Section: Introductionmentioning
confidence: 97%
“…Extremely interesting results (Tc: ~14 K for the ~30 nm thick film) have been reported using TBTDEN/H 2 [15,18] or TBTDEN/H 2 /N 2 [17,19]. Several authors [14,18] reported that the films may contain relatively high amounts of oxygen and carbon, up to 50 at%. However, high impurity levels make it difficult to make definite conclusions on the relationship between material properties and the superconductivity.…”
Section: Introductionmentioning
confidence: 97%
“…NbN thin films are generally fabricated by reactive magnetron sputtering [4], high-temperature chemical vapor deposition technique (HTCVD) [5] or atomic layer deposition (ALD) [6]. Olaya et.…”
Section: Introductionmentioning
confidence: 99%
“…[5] fabricated 40 nm thin NbN film with T c = 16.8 K at sapphire by using of high-temperature chemical vapor de-position technique with the high substrate temperature (T s ) of 1300 • C, which makes this technology unusable for the preparation of heterostructures. On the other hand, Linzen [6] reported the fabrication of high quality 40 nm thick NbN film deposited by plasma-assisted ALD with relatively lower substrate temperature of T s = 350 • C on sapphire, but with lower T c of 13.8 K.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that TMN are attractive because of the combination of properties that makes them very suitable and reliable for different technological applications. From the perspective of electrical behavior, one TMN widely studied is niobium nitride (NbN), which exhibits very attractive electrical properties, mainly related to its superconducting behavior . Regarding this nitride, studies have mainly focused on determining the relationship between its electrical behavior and its microstructural state.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of electrical behavior, one TMN widely studied is niobium nitride (NbN), which exhibits very attractive electrical properties, mainly related to its superconducting behavior. 13 Regarding this nitride, studies have mainly focused on determining the relationship between its electrical behavior and its microstructural state. For example, Wang et al 14 reported that, at certain synthesis parameters, the NbN films, with the highest quality single crystal structure, exhibited the best superconducting properties.…”
Section: Introductionmentioning
confidence: 99%